Translating transitions thinking and transition management into the city planning world. - Walsh, Peter (Springer, 2018)
City planning draws out relationships between land use patterns, housing form and density, transport, energy provision and other infrastructures. While commonly struggling with the task, a city's planning system could be one of the key integrating forces for tackling the sustainability challenge. As it happens, these particular systems are quite regularly subject to coordinated and relatively well resourced reform efforts, usually not generated from a sustainability viewpoint. This chapter raises the question of whether, and how, transition management ideas might more directly enter and influence this "turbulent" reform space. Sydney provides the case-setting for the introduction of transition management, and related conceptions, to a recent major planning system reform project for that city. Working from a theoretical meshing of planning, relational-institutional and transitions studies, a new process model for planning system reform projects is introduced: the Planning System Transition (PST) framework. This framework's development and testing, through empirical research, is explained. This chapter suggests positive prospects for transition management in city planning reform, but also highlights the critical requirement for contextualisation with practical and scholarly planning insights, as exemplified in the PST framework.
Keywords: Nachhaltige Stadtentwicklung; Planungstheorie; Planungspraxis